2021
DOI: 10.48161/qaj.v1n2a52
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Data Mining Implementation in Smart City Applications

Abstract: Many policymakers envisage using a community model and Big Data technology to achieve the sustainability demanded by intelligent city components and raise living standards. Smart cities use different technology to make their residents more successful in their health, housing, electricity, learning, and water supplies. This involves reducing prices and the utilization of resources and communicating more effectively and creatively for our employees. Extensive data analysis is a comparatively modern technology th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 51 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…Additionally, the high courts of clinical medicine changes patients' behaviours towards the medical services and affects the poverty stricken patients who would not afford the plans which are actually needed for the patients for long term cure. It is an immensely obvious factor that the patient who would not be able to afford the medical services which are highly costly to be afforded, they would not recommend the plans to others because of the rated plans and services within that particular organization [13]. These particular issues related to the healthcare sectors and services can leads an complicated challenge which can affects the mental health of the patient and can affect the stability of the healthcare services in a certain pace.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the high courts of clinical medicine changes patients' behaviours towards the medical services and affects the poverty stricken patients who would not afford the plans which are actually needed for the patients for long term cure. It is an immensely obvious factor that the patient who would not be able to afford the medical services which are highly costly to be afforded, they would not recommend the plans to others because of the rated plans and services within that particular organization [13]. These particular issues related to the healthcare sectors and services can leads an complicated challenge which can affects the mental health of the patient and can affect the stability of the healthcare services in a certain pace.…”
Section: Resultsmentioning
confidence: 99%
“…Development Mechanisms. First, it is argued through the theory of enterprise resource foundation that big data resources have been widely valued and protected by enterprises as a key fundamental resource [14]. eoretically, enterprises need to enhance their utilization of basic resources in the process of development and operation.…”
Section: Methodological Design For Big Data Analysis Of Enterprisementioning
confidence: 99%
“…rough the search of well-known websites, such as Dangdang.com and Joyo.com, it was found that domestic scholars have published a series of books related to smart tourism and smart city research, which enriched the theoretical research on smart tourism [8]. By studying the role of digital information technology in the distribution of urban tourism industry, researchers create an urban information system supported by digital technology to support urban development, and they also create a systematic, scientific, and comprehensive decision-making basis for government tourism decision-making departments [9].…”
Section: Related Workmentioning
confidence: 99%